Increased dosage of cyclosporine induces myopathy with increased seru creatine kinase in an elderly patient on chronic statin therapy. (16th December 2014) - Mo, L.; He, J.; Yue, Q.; Dong, B.; Huang, X.
Summary What is known and objective The concomitant administration of atorvastatin and cyclosporine has been shown to increase the serum concentration of 3‐hydroxy‐3‐methylglutaryl coenzyme A, which may be associated with the elevation of creatine kinase and an increased risk of myopathy. Our objective is to report on a case of statin‐induced myopathy associated with concomitant use of cyclosporine and other contributing factors. Case summary An 88‐year‐old Chinese male patient with comorbidities received polypharmacy treatment, including atorvastatin and cyclosporine. After the dosage of cyclosporine was increased to 300 mg every day for 8 months, the patient developed body pain and leg weakness, with a serum creatine kinase increase and evidence on magnetic resonance imaging of muscle oedema. What is new and conclusion Cyclosporine is a moderate inhibitor of the cytochrome P450 CYP3A4 isoenzyme, which is known to increase the serum level of atorvastatin. We hypothesized that the pharmacological and pharmacokinetic properties of atorvastatin‐induced myopathy are the result of its interaction with high dosage of cyclosporine.